PENINGKATAN KETERAMPILAN LOUD READING MENGGUNAKAN WORD-CARD-MEDIA KELAS II SD 29 AMBAWANG - Susanti, Susanti; Kaswari, Kaswari; Margiati, K.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractA common problem in this research is "Will the word card media can improve loud reading skill in grade III SD Sungai Ambawang?". This research uses descriptive method with research form of class action and nature of collaborative research. people consisting of 12 male students and 8 female students. The research technique used the technique of direct observation of measurement techniques with data collection tools in the form of observation sheet and test sheet in the form of poetry text. Data presentation techniques in the form of tables and data analysis to find scores of teacher ability to design and implement learning, and percentage of students reading skills. The research results using word card media has increased. For scores of teacher ability to plan lessons in cycle I (average 2.98), cycle 2 (average 3.42), there is an increase of 0.44 and in cycle 3 (average 3.85) there is an increase of 0.43. The ability of teacher in conducting learning cycle I (average 2.96), cycle 2 (average 3.42), there is an increase of 0.46 and in cycle 3 (average 3.83), there is an increase of 0 , 41. While on the students' reading skill cycle 1 (average 36,36%) cycle 2 (mean 60,61%) there was an increase of 24,25, and in cycle 3 (average 78,79%) there was improvement of 18.18%. Therefore, it can be said there is an increase in the ability of teacher in planning and implementing learning, and there is improving students loud reading skills in learning Indonesian language by using word card media. Keywords:       Loud Reading Skills, Word Card Media